Cost–utility analysis of tenofovir disoproxil fumarate in the treatment of chronic hepatitis B - Dakin, H; Bentley, A; Dusheiko, G (Elsevier, 2011)
Objective The aim of this study was to assess the cost-effectiveness of tenofovir disoproxil fumarate (TDF) in the treatment of chronic hepatitis B (CHB) versus alternative nucleos(t)ides from a UK National Health Service (NHS) perspective.